Increasing Awareness and Readership of Tribun Jateng Newspaper as Production Manager - Lana Nastiti Mumpuni; Djoko Setyabudi, S.Sos, MM (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Tribun Jateng is a subsidiary of Kompas Gramedia Group, which has its headquarters in Semarang. At first, the name of newspaper is still callled Warta Jateng with the slogan